MODERN APPROACHES AND INNOVATIONS IN TEACHING ENGLISH IN PRIMARY SCHOOL (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides information on the use of modern approaches and innovative methods in teaching English in primary grades, the development of students' ability to think logically, the formation of fluency in speech, the ability to quickly and correctly answer, and the efforts to thoroughly prepare for classes as a result of the development of passion for knowledge.